What is in a Blood Group? ABO and Rh Blood Types in COVID–19: Correlation with Clinical Outcomes in A Tertiary Care Centre in India - Muralidhar, Aparna; Shetty, Archana; Gaffoor, Nidha; Sandeepa, Supriya; Sandhyarani, Kanna; Nagabhushan, Bhargavi Kalburgi (International Journal of Human and Health Sciences (IJHHS), 2022)
Background: COVID-19 pandemic has immensely burdened healthcare. Susceptibility and severity of infection though largely determined by an individual’s immunity, age and comorbidities; however, recent literature reported that ABO blood type might be a contributory factor by virtue of its antigenic properties. Objective: To explore the distribution of ABO & Rh blood types in COVID -19 patients and correlate the same with clinical severity and mortality. Methods: This retrospective study was conducted from May 2020 to September 2021 at a tertiary care centre. Data of ABO & Rh blood type of COVID-19 patients admitted to our hospital was collected. Details on severity and mortality was obtained from hospital database. Pearson’s chi square test was used to compare categorical data. p-value<0.05 was considered statistically significant. Results: A total of 548 cases were included, with mean age of 48.8 ±7.1 years and male predominance. O positive (45.1%) and A negative (0.7%) were most and least frequently affected respectively. Majority were Rh positive (96.0%). 143 were severely ill requiring intensive care. Among the fifty-six deceased, most belonged to O blood group. No significant association was observed between blood type with severity/mortality. Conclusion: ABO blood type cannot be a pivotal biomarker for predicting COVID-19 associated severity and mortality. With limited literature in this field revealing diverse findings, a definitive association between blood type and COVID-19 is challenging. This may indicate unexplored underlying contributing factors, not necessarily blood group or type of antibodies present. International Journal of Human and Health Sciences Vol. 06 No. 04 Oct’22 Page: 432-437